STRUCTURE OF TROPICAL FOREST ECOSYSTEM HISTORY AND DEVELOPMENT - A REVIEW - Manh Hung, Bui (Journal of Forestry Science and Technology, 2018)
In recent decades, forest area in Vietnam has significantly decreased. The forest lost has decreased the number of species and influenced the forest quality in terms of structure, timber volume and biodiversity. Forest structure plays an important role in forestry research. Forest structure greatly impacts the habitat of fauna and flora species. Complex forest structures diversify microclimates, niches and habitats for creatures. Forest structure is the key to understanding and determining ecosystem functions. This article provides a full picture about the history and development of overstorey structure analysis for forest ecosystems. Before the 16th century, a pioneer of knowledge about tropical forests for Europeans was Alexander the Great, when he visited the Khyber Pass in 327 BC. In 16th and 17th centuries, there were more voyages and European colonial expansion such as: Francis Drake and English. Now, the study of the rainforest canopy structure can be divided into five categories based on canopy definition and scale. There are five types: the collection of all crowns, the whole volume between upper and lower crowns, the collection of crowns touching the canopy surface, the whole volume between the canopy surface crowns and the whole above-ground forest volume. Many attributes have analyzed such as: foliage, canopy cover, tree diameter, tree height, tree spacing, stand biomass, tree species and dead wood. These analyses are valuable bases to manage the forest ecosystem sustainably in the future.